Klasifikasi Pertumbuhan Penduduk Kota Malang Menggunakan Hibridasi Algoritme Genetika dan Jaringan Syaraf Tiruan - Obed Manuel Silalahi; Imam Cholissodin; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Population is one of the common problems that developed into a problem for developing countries including Indonesia. Malang, which is part of Indonesia, is known as a city of education and tourism that is sufficient to increase the population. These requirements certainly need special attention for the relevant parties to carry out certain policies in order to support population turnover. One thing that can be done is the classification of population growth based on age groups that can be done by the system efficiently. Based on this, we need a system that has scientific computing capabilities in its application. Backpropagation is a method of Artificial Neural Networks which is quite popular and helps to be used in data classification. This method can be combined with genetic algorithms in the optimization process of initial weights v and w. The ideal parameters obtained from the test include: K-fold = 8, a combination of the bipolar approval function, the number of generations of 10, the population number 75, the value of Cr = 0.8 and the value of Mr = 0.2, the number of iterations used 100, alpha value of 0.1 and hidden neurons 2 with the resulting accuracy of 92.86%.